Osimertinib versus osimertinib plus chemotherapy for non–small cell lung cancer with EGFR (T790M)-associated resistance to initial EGFR inhibitor treatment: An open-label, randomised phase 2 clinical trial. (May 2021) - Tanaka, Kentaro; Asahina, Hajime; Kishimoto, Junji; Miyata, Yoshihiro; Uchida, Takahiro; Watanabe, Kana; Hamai, Kosuke; Harada, Taishi; Tsubata, Yukari; Sugawara, Shunichi; Kobayashi, Kunihiko; Sugio, Kenji; et al.
Abstract: Background: Osimertinib is now a standard treatment for patients with previously untreated EGFR -mutated advanced non–small cell lung cancer (NSCLC). We here investigated whether the combination of osimertinib with cytotoxic chemotherapy might hold additive efficacy, as well as tolerability. Patients and methods: We conducted an open-label randomised phase 2 study to evaluate osimertinib and carboplatin-pemetrexed combination in comparison with osimertinib monotherapy in EGFR mutation–positive NSCLC patients who experienced disease progression associated with the emergence of the T790M resistance mutation of EGFR during first-line EGFR-TKI therapy. The primary endpoint was PFS, with secondary endpoints, including OS, response, and safety. Given that osimertinib was approved as a first-line treatment during the study, patient accrual was discontinued, and a final analysis was performed for the 62 enrolled patients. Results: Median PFS was 15.8 months for the osimertinib monotherapy group and 14.6 months for the combination therapy group (hazard ratio of 1.09, with a 95% confidence interval of 0.51–2.32; P  = .83). Median OS was not reached in either group. The overall response rate was 71.4% in the osimertinib monotherapy group and 53.6% in the combination group. The frequency or severity of known adverse events in the combination group was comparable to those with carboplatin and pemetrexed previously reported, and novel adverse events were not observed in this study. Conclusion: This is the first randomised study to investigate the efficacy and safety of the combination of osimertinib and cytotoxic chemotherapy for EGFR -mutated NSCLC. The addition of chemotherapy to osimertinib as a second-line treatment did not prolong survival, while it was found to be generally tolerable. This combination strategy will be further validated in the first-line setting. Trial registration: Japan Registry of Clinical Trials (jRCT) identifier: jRCTs071180062. Highlights: Combination of osimertinib and cytotoxic chemotherapy has not been yet investigated. This randomised trial evaluated concurrent osimertinib and carboplatin-pemetrexed. PFS, a primary endpoint, was similar between osimertinib group and combination group. The combination of osimertinib and cytotoxic chemotherapy was found to be tolerable.